Daur Al Takayyuf Al Lughawī Fī Al Tarjamah Bayna Al Indūnīsiyyah Wa Al ‘Arabiyyah: Dirāsah Taqābuliyyah Naḥwiyyah - Azmy Ali Muchtar; Ibnie Syahid Ahabi; Taufik Hidayat Hidayat; Soraiya Utsman Utsman (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
This study examines the importance of distinguishing between genitive constructions (iḍāfah) and descriptive phrases (na‘t) in Arabic-Indonesian translation and their impact on accuracy. It highlights structural and semantic differences between the two languages, which often lead to errors when translators misinterpret the relationships between phrases. Arabic relies on clear grammatical patterns such as possession and agreement, while Indonesian depends more on context and word order. The study finds that many translation inaccuracies stem from limited understanding of these distinctions and overreliance on literal translation. It emphasises the need for comparative linguistic analysis in teaching to help learners better recognise and apply these structures. Additionally, exposure to authentic texts is recommended to improve contextual awareness and translation sensitivity. The research also discusses the role of modern technology, including machine translation and artificial intelligence, in enhancing efficiency. However, it stresses that such tools cannot replace human expertise, as grammatical and contextual knowledge remain essential for evaluating and refining outputs. Overall, improving translation quality requires a balanced approach that integrates structural understanding, semantic awareness, practical training, and effective use of technological tools.